2009
DOI: 10.1095/biolreprod.108.074955
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2A Has a Novel Variant in Fish Oocytes1

Abstract: Histone variants and their modification have significant roles in many cellular processes. In this study, we identified and characterized the histone H2A variant h2af1o in fish and revealed its oocyte-specific expression pattern during oogenesis and embryogenesis. Moreover, posttranslational modification of H2af1o was observed that results from phosphorylation during oocyte maturation. To understand the binding dynamics of the novel core histone variant H2af1o in nucleosomes, we cloned ubiquitous gibel carp h2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 55 publications
0
19
0
1
Order By: Relevance
“…Gibel carp, because of the polyploid background and dual reproduction modes of gynogenesis and sexuality, has become a promising fish for screening and isolating reproduction-related genes that are involved in primordial germ cell formation, oocyte maturation and egg fertilization. Using suppression subtractive hybridization and protein purification [51,52], some important genes, such as germ plasm markers vasa [53] and Dazl [54], oocyte maturation-related factors cyclin A2 [55], C-type lectin [52], C1q-like [56][57][58], histone H2A variant h2af1o [59], and maternal-effect factor spindlin [60], have been identified and functionally characterized from gibel carp. For example, Sun et al [61] have observed oocytespecific expression pattern and dynamic distribution of Spindlin during oocyte maturation and egg fertilization, demonstrated its association and interaction with β-tubulin and spindle, and found that its elimination destroys spindle assembly, and thereby disturbs the oocyte-to-embryo transition and first cleavage, which provided the first direct evidence for the critical oocyte-to-embryo transition function of Spindlin in vertebrates.…”
Section: Reproduction Trait and Candidate Reproductionrelated Genesmentioning
confidence: 99%
“…Gibel carp, because of the polyploid background and dual reproduction modes of gynogenesis and sexuality, has become a promising fish for screening and isolating reproduction-related genes that are involved in primordial germ cell formation, oocyte maturation and egg fertilization. Using suppression subtractive hybridization and protein purification [51,52], some important genes, such as germ plasm markers vasa [53] and Dazl [54], oocyte maturation-related factors cyclin A2 [55], C-type lectin [52], C1q-like [56][57][58], histone H2A variant h2af1o [59], and maternal-effect factor spindlin [60], have been identified and functionally characterized from gibel carp. For example, Sun et al [61] have observed oocytespecific expression pattern and dynamic distribution of Spindlin during oocyte maturation and egg fertilization, demonstrated its association and interaction with β-tubulin and spindle, and found that its elimination destroys spindle assembly, and thereby disturbs the oocyte-to-embryo transition and first cleavage, which provided the first direct evidence for the critical oocyte-to-embryo transition function of Spindlin in vertebrates.…”
Section: Reproduction Trait and Candidate Reproductionrelated Genesmentioning
confidence: 99%
“…Mei et al [58] revealed the biological function that zebrafish C1q-like inhibits p53-mediated apoptosis and controls normal hematopoiesis during embryogenesis. Recently, Wu et al [59] identified a novel oocyte-specific core histone H2A variant in fish including gibel carp, and revealed the intrinsic ability to modify chromatin properties by fluorescence recovery after photobleaching (FRAP). They cloned and characterized a nucleophosmin/nucleoplasmin homolog from gibel carp and crucian carp, and gave novel evidence for a functional commonality of nucleophosmin and nucleoplasmin by immunodepletion and in vitro sperm decondensation experiments [60].…”
Section: Gene Identification Involved In the Reproduction And Early Dmentioning
confidence: 99%
“…Among them, histones and their associated proteins are the most abundant maternal factors (Arnold et al, 2008;Xu et al, 2010). Oocytespecific histones, such as oocyte-specific H2A variant H2af1o in fish species Carassius gibelio and Danio rerio (Wu et al, 2009;Zhao et al, 2011;Yue et al, 2013), linker histone H1 B4 in Silurana tropicalis (Smith et al, 1988), and H1foo in mammal species Mus musculus and Bos taurus (Tanaka et al, 2001(Tanaka et al, , 2005McGraw et al, 2006;Furuya et al, 2007), have been identified in vertebrates.…”
Section: Introductionmentioning
confidence: 99%